Localizing Modern Female Subjectivities: World Society and the Spatial Negotiation of Gender Norms in Turkey. (May 2016) - Yüksel, Gökçen; Stetter, Stephan; Walter, Jochen
In our article, we analyze gender norms in Turkey. We are interested in how such norms are transformed or reified in light of global/local interplays in contemporary world society. The case of Turkey is usually studied with a view to a persistent gap between national/global constitutional and legal provisions that promote gender equality, on the one hand, and a seemingly resistant everyday reality, on the other. While our research in the Turkish province of Hatay confirms that such a gap persists, we nevertheless detect meaningful transformations of gender norms in everyday practice. Our research, which focuses in women's positioning in higher education, indicates that such transformations occur in particular through everyday spatial practices, inter alia through what we refer to as local tactics of mobility by women seeking higher education. While there is no linear and direct diffusion of gender norms from the global/national to the local, we nevertheless observe significant global/local interplays to which these local norm transformations relate. These interplays can be well captured on the basis of constructivist theories of modernity. More specifically, by drawing from theories of world society and global governmentality, we conceive of these spatial practices as a diffusion of forms of (female) modern subjectivities, engendered by modern technologies of the Self, through which women in Hatay locate themselves in relation to a world society shaped by societal differentiation and social exclusion. Transformations or reifications of gender norms in Hatay are thus not so much the result of a direct diffusion of global gender norms. They are rather triggered indirectly through spatial practices on the local level that are, in turn, embedded within a world societal horizon that promotes modern subjectivities in response to societal differentiation and social exclusion.